UMP-CEC offered 300 job opportunities - UMP, PNC
Universiti Malaysia Pahang’s Career and Entrepreneur Carnival (UMP-CEC) organised by Student Affairs and Alumni (Saffad) received encouraging response as some 1,000 visitors thronged the event held at Astaka Hall from May 9-11, 2012.